Pre-registration nursing student’s knowledge and perception of MRSA - Quelch, Elizabeth (2009)
The infection prevention and control of MRSA has become a healthcare and government priority, as a result of the risk in presents to patient safety. The aim of this quantitative study was to investigate the knowledge and the perceived risk of contracting MRSA amongst pre-registration nursing students. The students were studying for a Masters of nursing science, a Bachelor of nursing or a Diploma of nursing, and were in their first, second, third or fourth year (only Masters students) of study. Difference in the knowledge and perceived risk between the students on the different courses and in different years was also investigated. A descriptive, cross sectional questionnaire was used as a method of obtaining the data.